Evaluación de la infectividad de aislamientos de rizobios nodulares de Lathyrus parodii inoculados en Vicia villosa - Jung, Cristobal; Ben Guerrero, Emiliano; Noguera, Justo Maximiliano; Morales, Matias; Piccinetti, Carlos Fabian (ALAR, 2025)
Poster